Pengkajian Mikroba Probiotik Lokal dan Pupuk NPK Kujang Terhadap Hasil Padi Varietas Inpari 13 - PERMADI, KARSIDI; SUNANDAR, BAMBANG; PURNAMASARI, NENENG RATNA (Agrotrop : Journal on Agriculture Science, 2014)
The increase of rice production by using the approach of integrated crop and resource management (ICM) besides high yielding varieties (HYV), inorganic compound fertilizer which followed the return of insitu rice straw instead of compost or manure. However, this in situ rice straw should be treated by local probiotic microbes so the straw becomes decayed and fragile that facilitates the land processing. This study aimed to determine the effect of the addition of Kujang NPK fertilizer with local probiotic microbes on rice yield of Inpari 13 variety in irrigated land. This study uses a separate plot design with 5 replications. The main plot is the gift of local probiotic microbes (Agri Super and Agri Simba), and the subplot is the addition of Kujang NPK fertilizer (200, 300, and 400 kg/ha). The results of this study show that there are no interaction influence occurs between the addition of Kujang NPK fertilizer with the administering local probiotic microbes on plant height at harvest, yield components and dried grain yield. The highest dried grain yield by administering of Agri Super is 8.59 t ha-1. The addition of Kujang NPK fertilizer at dose 300 kg ha-1 gave the highest grain yield as much as at dose 8.24 t ha-1, and the lowest yield achieved at doses of 200 kg ha-1 of Kujang NPK approximately 7.55 t ha-1.
Keywords: Kujang NPK Fertilizers, Local Probiotic Microbes, Inpari 13